APPLICATION INFORMATION GUIDE MOUNTAIN CLIMBING 6.0 USING MICROSOFT VISUAL BASIC - Heru Prasetyo; Sahni D. P., SKom, MMSI Sahni D. P., SKom, MMSI (Jurnal Sistem Informasi, 2003)
Today's increasingly rampant activities of mountain climbing conducted by theteenagers, both sons and putrid. The frequency of these activities will appearprominently on each long vacation in high school and college students. Mountainclimbing is one sport in the wild adventure that must have technical knowledge aboutthe terrain, climbing lane, weather, and how to preserve life in the wild.Mountain climbing is not a recreational activity and entertainment, because iteliminates a human life at risk. Disaster that claimed the lives climbers frequentlyoccur, whether caused by natural factors or if the human factor itself. Especially forthose who do not have specialist knowledge in sport climbing. In this case,preparation is needed before doing this mountaineering activities.Application is made to provide information about the mountain climbing guide. Thisapplication was built using Microsoft Visual Basic 6.0 with the intention that thisapplication can display the character of the user interface or in other words can beunderstood easily by the user.